ANALISIS ATRIBUT KEAMANAN TERHADAP PERBAIKAN PROTOKOL GROUP KEY TRANSFER : PROTOKOL HSU - I Made Mustika Kerta Astawa; Rahmi Nurazizah (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
Protocol Hsu et.al first introduced in 2012 and is the protocol type Group Key Transfer based Linear Shamir's Secret Sharing Scheme (LSSS). The main idea of this protocol is to use m-secret sharing perspective. This protocol assumes that the difficulty of discrete logarithm problem (DLP) (ie given is computationally very difficult/not feasible to count ) and Cryptographyc Diffie Hellman (CDH) (ie given and it is computationally very difficult/not feasible to count ) in . Thus, it needs to analyze the security attributes to this mechanism Protocol Hsu. Good cryptographic protocols should meet the security attributes Known Security Key, Key-Compromise Impersonation Resillience, Unknown Key-Share Resillience, Key Control and Key Confirmation.